2013
DOI: 10.1016/j.physletb.2013.10.071
|View full text |Cite
|
Sign up to set email alerts
|

Note on the super-inflation in loop quantum cosmology

Abstract: Phenomenological effect of the super-inflation in loop quantum cosmology (LQC) is discussed. We investigate the case that the Universe is filled with the interacting field between massive scalar field and radiation. Considering the damping coefficient Γ as a constant, the changes of the scale factor during super-inflation with four different initial conditions are discussed, and we find that the changes of the scale factor depends on the initial values of energy density of the scalar field and radiation at the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 29 publications
0
23
1
Order By: Relevance
“…Although the scale factor a increases very fast when one considers the initial condition that the potential energy dominates at the bounce point, the change rate of a is still less than e 60 . This result is different from [29], in which we found that it is possible to get e-folding number during the super inflation of the interacting scalar field and radiation, i.e., the change rate of scale factor a is bigger than e 60 if the potential energy dominates at the bounce point [29].…”
Section: A Super Inflationcontrasting
confidence: 79%
See 2 more Smart Citations
“…Although the scale factor a increases very fast when one considers the initial condition that the potential energy dominates at the bounce point, the change rate of a is still less than e 60 . This result is different from [29], in which we found that it is possible to get e-folding number during the super inflation of the interacting scalar field and radiation, i.e., the change rate of scale factor a is bigger than e 60 if the potential energy dominates at the bounce point [29].…”
Section: A Super Inflationcontrasting
confidence: 79%
“…This means the universe will enter an super inflation stage as soon as the bounce begins, and it will last untilḢ = 0, i.e., ρ = 1 2 ρ c . There are lots of studies discuss the properties of super inflation [24][25][26][27][28][29]. As we know, to get enough e-folding number, the scale factor should increase very fast in slow-roll inflation stage to ensure the e-folding number N > 60.…”
Section: A Super Inflationmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, the arofementioned analysis points that the (1 − ρ/ρ c ) term, imposes a specific era of inflation 0 < H < H I , where for ρ ρ c the universe enters in the inflationary phase, while the characteristic scale H I presumably connected to a scale which is around to that of the Grand Unified Theory (GUT). Overall, the condition H = 0,Ḣ > 0 implies that the Universe enters in the LQC inflationary era at the bounce point [39] (see also [40]). Unlike nominal (cold) inflation, in which H const., here the key point is to understand that the Hubble parameter varies with time.…”
Section: Loop Quantum Cosmology Versus Warm Inflationmentioning
confidence: 99%
“…In our model the condition = 1 makes sure that inflation starts at the earliest possible stage [76,80]. As far as the number of e-folds is concerned we have (39) or (40) where for the last equality we used Eq. (24).…”
Section: The Strong Dissipative Regime and Slow-roll Parametersmentioning
confidence: 99%